2022
DOI: 10.1155/2022/9666963
|View full text |Cite|
|
Sign up to set email alerts
|

Pravastatin Reduces Matrix Metalloproteinases Expression and Promotes Cholesterol Efflux in Osteoarthritis Chondrocytes

Abstract: Background. Chondrocyte metabolic disorder plays an important role in the development of osteoarthritis (OA). The use of statins in the treatment of OA has also been widely studied, but the mechanism is still confusing. The present study aims to investigate the effects of statin on osteoarthritis chondrocytes and its underlying mechanism. Major findings. An untargeted metabolomics study revealed that the treatment of statins significantly changed the metabolites of articular cartilage tissues collected from fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Similarly, atorvastatin increased cholesterol efflux by promoting foam cell lipophagy (Zheng et al, 2021). Furthermore, pravastatin enhanced cholesterol efflux in chondrocytes (Wu et al, 2022). In summary, the effect of statin therapy on HDL functionality would depend on the statin employed and the target organ.…”
Section: Statinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, atorvastatin increased cholesterol efflux by promoting foam cell lipophagy (Zheng et al, 2021). Furthermore, pravastatin enhanced cholesterol efflux in chondrocytes (Wu et al, 2022). In summary, the effect of statin therapy on HDL functionality would depend on the statin employed and the target organ.…”
Section: Statinsmentioning
confidence: 99%
“…Furthermore, the combination of β-cyclodextrin and simvastatin-loaded rHDL in a sink/shuttle structure showed remarkable capacity to promote cholesterol efflux and decrease inflammation in macrophages (He et al, 2020). Importantly, the effect of statins on HDL functionality could extend beyond CVD therapy and be useful for the treatment of certain cancers and conditions such as osteoarthritis and glaucoma (Wu et al, 2022;Yang et al, 2022b;Yang et al, 2023).…”
Section: Statinsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%